Cellulolytic Bacteria Associated with Gut of Longhorn Beetle, Prionomma bigibbosum (Coleoptera: Cerambycidae): an Electron Microscopic Study: Cellulolytic Bacteria Associated with Gut of Prionomma bigibbosum - SUMITA BISWAS; DIBYENDU PAUL; ATANU BHATTACHARJEE (Journal of Tropical Life Science, 2022)
Adult Cerambycid (sub-family Prioninae) beetles are non-feeders. The present study aims to investigate and evaluate the gastrointestinal microbiota in long horn beetle Prionomma (Ancyloprotus) bigibbosum White (1853) (Coleoptera: Crambycidae: Prioninae: Prionini) gut. Scanning electron micrograph revealed the presence of abundant bacteria firmly attached to hindgut. The gut flora were isolated and screened on Carboxymethylcellulose (CMC) agar medium using CMC as sole carbon source. The cellulolytic activity was measured both qualitatively and quantitatively. Cellulolytic efficiency was assessed by DNS method. Potent cellulose degrader bacterial isolate was subjected to phenotypic and genotypic characterization. A Gram positive, non-motile, oxidase positive coccoid isolate designated as PBI9 was found to be efficient cellulose degrader. Based on 16S rRNA gene analysis, the isolate was found to be most closely related to Mammaliicoccus fleurettii, Mammaliicoccus stepanovicii and Mammaliicoccus lentus (99.24%, 99.17% and 99.17% respectively) and was identified as Mammaliicoccus Â sciuri (99.86% similarity) (NCBI Accession number MZ351443). This appears to be first study undertaking SEM of gut microbiota of longhorn beetle, P. bigibbosum and to report the P. bigibbosum gut as a novel source of cellulolytic bacteria.